Metabolic fitness of Candida albicans is indispensable for functional drug efflux, ergosterol, and chitin biosynthesis - Sandeep Hans; Zeeshan Fatima; Saif Hameed (Mazandaran University of Medical Sciences, 2020)
Background and Purpose: The increment in fungal infections, particularly due to Candida species, is alarming due to the emergence of multidrug resistance (MDR). Hence, the identification of novel drug targets to circumvent the problem of MDR requires immediate attention. The metabolic pathway, such as glyoxylate cycle (GC), which utilizes key enzymes (isocitrate lyase [ICL] and malate synthase [MLS]), enables C. albicans to adapt under glucose-deficient conditions. This study uncovers the effect of GC disruption on the major MDR mechanisms of C. albicans as a human pathogenic fungus. Materials and Methods: For the purpose of the study, efflux pump activity was assessed by phenotypic susceptibilities in the presence of substrates rhodamine 6G (R6G) and Nile red, along with R6G extracellular concentration (527 nm). In addition, ergosterol content was estimated by the alcoholic potassium hydroxide hydrolysis method. The estimation of chitin was also accomplished by the absorbance (520 nm) of glucosamine released by acid hydrolysis. Results: The results revealed that the disruption of ICL enzyme gene (Δicl1) led to the impairment of the efflux activity of multidrug transporters belonging to the ATP-binding cassette superfamily. It was further shown that Δicl1 mutant exhibited diminished ergosterol and chitin contents. In addition, all abrogated phenotypes could be rescued in the reverting strain of Δicl1 mutant. Conclusion: Based on the findings, the disruption of GC affected efflux activity and the synthesis of ergosterol and chitin. The present study for the first time revealed that metabolic fitness was associated with functional drug efflux, ergosterol and chitin biosynthesis and validated GC as an antifungal target. However, further studies are needed to comprehend and exploit this therapeutic opportunity.